Glyphosate induced hormesis in Urochloa cultivars with sequential application - da Cunha Codognoto, Luciane; Amorim Faria, Glaucia [UNESP]; Luciene Maltoni, Katia [UNESP]; Telles Conde, Thassiane (FapUNIFESP (SciELO), 2023)
Glyphosate is the most widely used herbicide and is responsible for a significant technical/productive advance in world agriculture. Glyphosate drift after its application to control weeds in agricultural fields can stimulate growth and/or productive performance in non-target plants, located adjacent to the treatment, characterizing the hormesis effect. However, the hormesis effect of glyphosate may be different depending on the plant species, its stage of development, and the applied dose. Considering the stimulus of forage biomass production for animal feed, this study aimed to assess the hormesis effect by successive applications of low glyphosate doses to cultivars of the genus Urochloa. The shoot and root productive responses of three grass cultivars (Urochloa brizantha cv. Marandu, U. brizantha cv. Piatã, and U. ruziziensis cv. Ruziziensis) were assessed in pots through leaf applications of subdoses of the acid equivalent (ae) of glyphosate (5.40, 10.80, 21.60, 43.20, and 86.40 g ae ha-1) and a control (no glyphosate application). Four sequential harvests, conducted with a frequency of 21 days in a completely randomized design and a 6 x 3 x 4 factorial arrangement, with three replications, were assessed. Doses equal to or higher than 43.20 g ae ha-1 of glyphosate, applied in two sequential applications impaired the biomass production of the assessed forages. Ruziziensis was the most susceptible cultivar to the phytotoxic effect. Sequential applications of the subdoses 5.40 and 10.80 g ae ha-1 of glyphosate characterized the hormesis effect, promoting the shoot and root biomass production of the forage plants U. brizantha cv. Marandu, U. brizantha cv. Piatã, and U. ruziziensis cv. Ruziziensis.
Hormese induzida por glifosato em cultivares de Urochloa com aplicação sequencial
Keywords: acid equivalent; Drift; forage; hormesis; Urochloa